Measurement of Patient Experience towards Service Image at Abdoel Wahab Sjahranie Hospital - Suwanto Suwanto; Dwi Ida Puspita Sari; Nur Asiza (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2022)
Health is an important basic need for a decent and productive life in everyday life, which should belong to everyone. This type of research is an analytical survey with a cross-sectional research design, that is, research where data is collected only once to answer research problems. The population of this study was visitors who used health services at Abdoel Wahab Sjahranie Hospital during the study period. The study population through the average number of visits per month was 550 people, so the study sample was 227 people. The patient experience for the hospital's image has a good impact through nurse communication, physician communication, physical comfort and responsiveness. It is hoped that Abdoel Wahab Sjahranie Hospital will consistently maintain a work culture through good communication and governance in terms of hospital facilities and infrastructure